Nalākhyāna : upodghāta ane rasadarśī vivecana sāthe - Premānanda, 1636-1734 (SAMP early 20th-century Indian books project ;, 1951)
Verse work on Nala and Damayantī, Hindu mythological characters; includes critical introduction.